Character Education Based on Gender Justice in The Islamic Perspective - Suriadi Samsuri; Mursidin Mursidin; Mujahidin Mujahidin (Al-Hayat Al-Istiqomah Foundation, 2018)
Character educators are educated to form a person's personality through high education of character, which results in the back of someone's reality, namely good behavior, honesty, responsibility, respect for others, hard work, and so on. Gender differences are not really a problem as long as they do not give birth to discrimination. But in reality gender differences have given birth to various injustices, especially to women. Teachers who are held during this time are considered to be still many who are gender biased. These halghter can be found in the subject matter and in the treatment of female students in certain schools. From a material perspective, it can be seen in several book packages on student subjects, in which there is often a treatment that may not be accepted or has led to gender discrimination.Pendidik karakter dididik untuk membentuk kepribadian seseorang melalui pendidikan karakter yang tinggi, yang menghasilkan di belakang realitas seseorang, yaitu perilaku yang baik, kejujuran, tanggung jawab, rasa hormat terhadap orang lain, kerja keras, dan sebagainya. Perbedaan gender bukan masalah asalkan tidak melahirkan diskriminasi. Namun dalam kenyataannya, perbedaan gender telah melahirkan berbagai ketidakadilan, terutama bagi perempuan. Guru yang dipegang selama ini dianggap masih banyak yang bias gender. Halter ini dapat ditemukan dalam materi pelajaran dan perlakuan terhadap siswa perempuan di masing-masing sekolah. Dari perspektif fisik, dapat dilihat dalam beberapa paket buku tentang mata pelajaran siswa, di mana sering ada perlakuan yang mungkin tidak diterima atau mengarah pada diskriminasi gender.